EKSPLORASI ESTETIKA GARIS, WARNA, DAN DISTORSI VISUAL DALAM PING PONG THE ANIMATION DENGAN PENDEKATAN GAYA VISUAL GREAT PRETENDER - Abipraya Sujatmiko; Muh. Bahruddin; Krisna Yuwono Fora; Yunanto Tri Laksono (CandraRupa : Journal of Art, Design, and Media, 2026)
The Japanese animated film Ping Pong The Animation presents a non-conventional visual approach through the exploration of rough line work, expressive coloring, and formal distortion that challenges mainstream animation aesthetics. This visual style functions not only as an artistic identity but also as a narrative medium for representing the psychological dynamics, emotions, and inner conflicts of its characters. This study aims to analyze the aesthetics of line, color, and visual distortion in Ping Pong The Animation by employing the visual style of Great Pretender (2020) as a comparative framework. Great Pretender is selected due to its similar visual tendencies that emphasize extreme stylization, symbolic color palettes, and visual deformation as strategies for strengthening narrative and characterization. This research adopts a qualitative descriptive method with a visual analysis and animation stylistics approach. The data are collected through close observation of key scenes that represent the use of line, color, and visual distortion in both works. The analysis examines the relationship between these visual elements and their narrative functions, emotional atmosphere, and the construction of symbolic meaning. The theoretical framework is grounded in visual aesthetics theory, animation film stylistics, and visual semiotics. The findings indicate that Ping Pong The Animation employs dynamic and unstable line work to reflect the intensity of competition and the psychological states of the characters, while color is used selectively to emphasize specific emotional atmospheres. Visual distortion functions as an aesthetic strategy to express inner pressure, subjectivity, and character transformation. The visual style approach of Great Pretender demonstrates how similar stylization can produce different narrative effects through the use of more contrasting colors and theatrical visual compositions. This study concludes that the visual exploration in Ping Pong The Animation constitutes an effective cinematic language of animation that expands the possibilities of narrative expression through non-realistic aesthetics.